Akuntabilitas Pengelolaan Dana Bantuan Operasional Satuan Pendidikan (BOSP) (Studi Kasus Pada Sekolah Dasar Negeri 6 Sangsit Kecamatan Sawan Kabupaten Buleleng): (Studi Kasus pada Sekolah Dasar Negeri 6 Sangsit Kecamatan Sawan Kabupaten Buleleng) - Saputra, Komang Ari Widhi; Musmini, Lucy Sri (Universitas Pendidikan Ganesha, 2025)
This study aims to: 1) Know and describe the planning, implementation, supervision, and reporting of the management of BOSP funds at SD Negeri 6 Sangsit, Buleleng Regency; 2) Identify obstacles and efforts to overcome them in the management of these funds. The research used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation studies. Data analysis was conducted by data reduction, data presentation, and conclusion drawing.The results showed that: 1) The process of managing BOSP funds at SD Negeri 6 Sangsit has run well in accordance with the technical guidelines of Permendikbudristek No. 63 of 2023; 2) The main obstacles include delays in fund disbursement (overcome by bon to school partners) and changes in regulations (anticipated by rearranging reports according to the latest regulations).